Backscatter in a cloudy atmosphere as a lightning-threat indicator. (January 2015) - Kocifaj, Miroslav; Videen, Gorden; Klačka, Jozef
Abstract: We present a remote-sensing method for identifying electrically charged droplets in clouds. Our methodology utilizes the electromagnetic (EM) radiation backscattered by the cloud at multiple wavelengths. In general, the backscatter from collections of charged and neutral particles differs in Rayleigh regime. While a uniformly charged sphere can resonate with an incident EM radiation depending on electrostatic potential at the particle surface, the scatter by a neutral particle is governed by the Lorenz–Mie theory, thus resulting in different surface excitations. The effects of electric charges and other microphysical parameters on the electromagnetic interactions with particles are not easily separable. Because the spectral profile of the dielectric function for liquid water (or alternatively icy grains) is known, retrieval of net charges are possible based on the optical behavior of the backscattered EM signals. Such information can be used to determine charge build-up in the atmosphere, which is a condition for lightning. A basic configuration of a measuring system for lightning threats is discussed and described schematically. Highlights: Electrically charged and neutral particles scatter in a different way. Net surface charge on spherical particles is a modulator of backscatter signal. Radar echoes are source of information on electrically charged droplets. Remote-sensing method can be used to identify increased chance of lightning.